Análisis económico del rendimiento de los híbridos de maíz INHIAP H-551 y trueno nb 7443 mediante sistemas de labranza convencional y mínima y su impacto ambiental en el Cantón Mocache. - Quijije Rendón, Maritza Katheryn (2019)
The research was carried out in the rainy season of 2018, evaluating production costs in conventional and minimal tillage systems, using maize seeds of different provenance, on two farms near the "El tropezón" enclosure in the canton Mocache, whose overall objective was to economically analyse the performance of the hybrids INIAP H-551 and TRUENO NB 7443 in both farming systems under the conditions of the agricultural environment of the producer and their environmental impact. The comparative method allowed to estimate the different techniques applied in the cultivation of maize, to know the similarities and differences. The analytical method included the reasoning of the problems observed during the research, which generated the results obtained from the surveys carried out on the farmers of the two farms. From the investigation it was established that, using the hybrid "Thunder NB 7443", the production of maize reached 133 qq/ha, with an investment of $ 1,125.51; whereas, using the hybrid "INIAP H-551", the production achieved was 120 qq/ha, with an investment of $ 931,70; that is, through the minimum tillage system an additional investment of $ 193,81 was required to achieve an increase of 13 qq/ha of corn production; so it was evidenced in the calculations the utility for the INIAP H-551 of $ 388,30 and for the TRUENO NB 7443 $ 337,49. In conventional tillage, for every dollar invested, he earned $ 0,42; while, with minimal tillage, for every dollar invested he earned $ 0,30. As regards the environmental impact of the management of the two techniques, it was established that with the corn INIAP H-551, the farmer used 9 chemicals with a toxicological index of 2,33; unlike the maize TRUENO NB 7443, where the farmer used 10 chemicals with a toxicological index of 2,40. In other words, in both the minimal and conventional tillage system the producer Maicero used undesirable agrochemicals and therefore there was more pollution in the ecosystem. Key words: Technologies, systems of tillage, costs of production, profitability, economic and environmental impacts.